The Role of The Pesantren's Business Entity (Bump) in Improving the Economy of The Mawaridussalam Islamic Boarding School - Siregar, Ja’far Nawi A.; Imsar, Imsar; Silalahi, Purnama Ramadani; Yasfa, Afiq (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
The purpose of this research is to analyze how the role of the Pesantren-Owned Business Entity (BUMP) in improving the economy of the boarding school. In this research, the method used is a qualitative approach and is a field research. The results of this study show that the BUMP of Mawaridussalam Islamic boarding school plays an important role in improving the economy of the boarding school. In addition to student shops and student stalls as the largest contributor to profits, the boarding school is currently developing a business in agriculture which has started operating. The economic improvement of the Mawaridussalam boarding school is going well and in accordance with the increasing number of students. And the income of the boarding school has reached the BUMP annual income target of around + Rp 2,500,000,000.